Proteomic and metabolomic analyses reveal the novel targets of spermine for alleviating diabetic cardiomyopathy in type II diabetic mice - Sun, Jian; Xu, Jiyu; Liu, Yong; Xu, Xiaoyi; Zhang, Shumin; Hao, Yankun; Lin, Yitong; Han, Yue; Li, Feiya; Yuan, Hui (Frontiers in Cardiovascular Medicine, 2022)
Diabetic cardiomyopathy (DCM) is one of the most serious complications of diabetes. Recent cardiology studies suggest that spermine has a cardioprotective effect. Here, we used proteomic and metabolomic analyses to reveal the underlying research targets in a type II diabetic (T2D) mouse model treated with spermine. Left ventricular tissues from nine mice (Control group, three; T2D group, three; T2D+SP group, three) were excised and analyzed. Quantitative analysis of the global proteome and metabolome was performed using the 4D label-free technique and untargeted metabolomics, respectively, and differentially expressed proteins (DEPs) and metabolites were used to perform bioinformatic analyses. A total of 169 DEPs were identified in T2D/Control group, including 115 upregulated and 54 downregulated proteins. Furthermore, 16 DEPs were identified in T2D+SP/T2D group, where these DEPs were found highly enriched in the cellular, metabolic processes, biological regulation, response to stimulus, and immune system process. The results of association analysis between proteomics and metabolomics showed that SP could affect the production of 51 metabolites by regulating the expression of 16 DEPs in the T2D+SP/T2D group. We also found that PRKG1 was closely related to the expressions of 10 overlapping metabolites between db/db and SP-treated mice. Our findings provide insights into the underlying mechanisms for DCM and suggest the potential applicability of utilizing spermine on protecting against DCM-associated cardiac function deterioration.